2014
DOI: 10.1002/pits.21764
|View full text |Cite
|
Sign up to set email alerts
|

Examining Diversity Research Literature in School Psychology From 2004 to 2010

Abstract: One indicator of school psychology's capacity to provide culturally responsive practice is the percentage of articles in leading school psychology journals that have a “significant diversity focus.” To date, there have been three published empirical studies (Brown, Shriberg, & Wang, ; Miranda & Gutter, ; Rogers Wiese, ) that have defined and examined this construct. These three articles collectively provide empirical data on the percentage of articles appearing in leading school psychology journals that met cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The results indicated urban and rural school psychologists had little to no training on how to provide services to linguistic, racial, and economic minorities. These data reflect the multiple studies that have found most research in school psychology do not include minorities in the sample (Brown, Shriberg, & Wang, ; Gruenwald et al., ; Miranda & Gutter, ). Therefore, there were no statistically significant differences in the training between urban and rural school psychologists.…”
Section: Discussionsupporting
confidence: 58%
“…The results indicated urban and rural school psychologists had little to no training on how to provide services to linguistic, racial, and economic minorities. These data reflect the multiple studies that have found most research in school psychology do not include minorities in the sample (Brown, Shriberg, & Wang, ; Gruenwald et al., ; Miranda & Gutter, ). Therefore, there were no statistically significant differences in the training between urban and rural school psychologists.…”
Section: Discussionsupporting
confidence: 58%
“…To address this need, researchers and educators should consider behavior interventions that would target both social, emotional, and behavioral needs, as well as cultural roots of behavior differences, while reinforcing positive, expected behavior. A review of school psychology research published from 2004-2010 found that 15.5% of articles addressed racial, cultural, linguistic, sexual orientation, or socioeconomic diversity (Grunewald, et al, 2014). Of these 222 published reports, 15.3% addressed prevention or intervention for academic, behavioral, or social-emotional needs.…”
mentioning
confidence: 99%
“…Their analysis of five school psychology journals – Journal of Applied School Psychology , Journal of School Psychology, Psychology in the Schools , School Psychology Quarterly and School Psychology Review – found that 16.9% of the published research focused on diverse populations and of that, 2.9% focused on American Indian youth. Most recently, Grunewald et al (2014) content analyzed research published 2004 to 2010 using the same pool of school psychology journals as analyzed in Brown et al (2007) in addition to two more journals: Journal of Educational and Psychological Consultation and School Psychology Forum. They found just 0.9% of published research focused on American Indian youth, and like Brown et al , no mention of student strengths as a central subject of the research.…”
Section: Context and Rationalementioning
confidence: 99%